Development of a Multilayer Film Including the Soluble Eggshell Membrane Fraction for the Treatment of Oral Mucosa Lesions - Karthik Neduri; Giorgia Ailuno; Guendalina Zuccari; Anna Maria Bassi; Stefania Vernazza; Anna Maria Schito; Gabriele Caviglioli; Sara Baldassari (MDPI AG, 2024)
Background/Objectives: Oral diseases causing mucosal lesions are normally treated with local or systemic anti-inflammatory, analgesic and antimicrobial agents. The development of topical formulations, including wound-healing promoters, might speed up the recovery process, improving patients' quality of life, and reduce the risk of deterioration in health conditions. In this study, a mucoadhesive multilayer film, including a novel biocompatible substance (solubilized eggshell membrane, SESM), was rationally designed. Methods: The SESM preparation procedure was optimized and its biological effects on cell proliferation and inflammation marker gene expression were evaluated in vitro; preformulation studies were conducted to identify the most promising polymers with film-forming properties; then, trilayer films, consisting of an outer layer including chlorhexidine digluconate as a model drug, a supporting layer and a mucoadhesive layer, incorporating SESM, were prepared using the casting method and their mechanical, adhesion and drug release control properties were evaluated. Results: SESM proved to possess a notable wound-healing capacity, inducing a wound closure of 84% in 24 h without inhibiting blood clotting. The films revealed a maximum detachment force from porcine mucosa of approx. 1.7 kPa and maximum in vivo residence time of approx. 200-240 min; finally, they released up to 98% of the loaded drug within 4 h. Conclusions: The formulated trilayer films were found to possess adequate properties, making them potentially suitable for protecting oral lesions and favoring their rapid healing, while releasing antimicrobial substances that might be beneficial in reducing the risk of bacterial infections.